A bibliometric analysis of the graduate employability research trends - Nor Amirah Masduki; Mastura Mahfar; Aslan Amat Senin (Institute of Advanced Engineering and Science, 2022)
Graduate employability has received considerable attention over the years, owing to the labor market’s desire for highly skilled graduates. This study was to examine trends in graduate employability research from 1986 to 2020 through the use of a standard bibliometric procedure. During the study period, as many 343 documents were yielded from the Scopus database. The findings indicated that the relative growth rate of published article was 69 documents per year on average. Geographically, the United Kingdom ranked first as the most productive country, with 104 articles published. Between 2000-2010, the employability topic focused primarily on the role of higher education in providing appropriate career guidance and strategy development for graduates from both public and private institutions seeking employment. Between 2011-2019, the focus shifted to employability skills, work-integrated learning, and curriculum designs that are connected to the long-term enhancement of graduate employability and its impact on career goals. The findings of this study indicate a significant increase in graduate employability literature, as well as a significant number of citations. Academic researchers are encouraged to pursue development strategies that result in successful graduates finding employment in the labor market. This paper is innovative in that it identifies a trend and future for research in the field of employability.